Analysis of the Effect of Sustainable Business Practices on the Financial Performance of Manufacturing Companies in Jakarta: Case Study on Renewable Energy Use, Waste Management, and Environmental Economic Principles - Soelistianto, Farida Arinie; Nasirly, Riri; Sudarmanto, Eko; Cahya, Darmawan Listya (Westscience Press, 2023)
The adoption of renewable energy, waste management methods' efficacy, the application of environmental economic concepts, and the financial performance of manufacturing enterprises in Jakarta are all examined in this study. This study examined measurement models and structural models by analyzing data from 174 organizations using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings demonstrate that the company's profitability is considerably and favorably impacted by the use of environmental economic concepts and the deployment of renewable energy. This research highlights the significance of sustainable practices in attaining financial prosperity and provides useful guidance for companies seeking to manage the intricate terrain of ecological accountability and financial efficacy.